THE INFLUENCE OF MOTIVATION, LECTURER SUPPORT, AND LEARNING ENVIRONMENT ON ENGLISH PROFICIENCY THROUGH MARITIME TEXTBOOK MEDIATION - Muhamad Alfi Khoiruman; Mohd. Rafi Riyawi; Doni Hadi Irawan; Nina Ruly Istiari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the influence of learning motivation, lecturer support, and learning environment on English language proficiency for maritime work, with the English for Maritime textbook serving as a mediating variable among students at the Maritime Academy of Banyuwangi. Employing a quantitative approach with a cross-sectional survey design, data were collected from 178 respondents selected through proportionate stratified random sampling. The research instrument used a five-point Likert scale questionnaire, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The outer model evaluation confirmed convergent and discriminant validity, with all factor loadings above 0.70, Cronbach’s Alpha and Composite Reliability exceeding 0.70, and AVE values above 0.50. The inner model evaluation revealed R-square values of 0.45 for the English for Maritime textbook and 0.62 for English proficiency, indicating moderate to substantial explanatory power. Hypothesis testing through bootstrapping demonstrated that learning motivation, lecturer support, and learning environment significantly influenced English proficiency, both directly and indirectly, through the mediating role of the textbook. Among the predictors, motivation showed the strongest direct effect, while the textbook demonstrated a significant mediating contribution. These findings highlight the importance of integrating motivational strategies, lecturer engagement, and supportive environments with context-specific instructional materials to enhance English language competence for international maritime communication.